Problems of implementing the circular economy model in Ukraine - Okseniuk, Yulia; Huliaiev, Vitalii; Korniienko, Iryna; Yastremska, Larysa; Kovalenko, Alla; Filimonenko, Olha; Korniienko, Yurii (Problems of Environmental Biotechnology, 2024)
The issue of implementing the circular economy model in Ukraine is considered